Clinical Performance of the Xpert® CT/NG Test for Detection of Chlamydia trachomatis and Neisseria gonorrhoeae: A Multicenter Evaluation in Chinese Urban Hospitals - Han, Yan; Shi, Mei-Qin; Jiang, Qing-Ping; Le, Wen-Jing; Qin, Xiao-Lin; Xiong, Han-Zhen; Zheng, He-Ping; Tenover, Fred C.; Tang, Yi-Wei; Yin, Yue-Ping (Frontiers in Cellular and Infection Microbiology, 2022)
Background We aimed to evaluate the clinical performance of the GeneXpert® (Xpert) CT/NG assay for the detection of Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) using urine and cervical swabs collected from patients in China. Methods This study was conducted from September 2016 to September 2018 in three Chinese urban hospitals. The results from the Xpert CT/NG test were compared to those from the Roche cobas® 4800 CT/NG test. Discordant results were confirmed by DNA sequence analysis. Results In this study, 619 first void urine (FVU) specimens and 1,042 cervical swab specimens were included in the final dataset. There were no statistical differences between the results of the two tests for the detection of CT/NG in urine samples (p > 0.05), while a statistical difference was found in cervical swabs (p < 0.05). For CT detection, the sensitivity and specificity of the Xpert test were 100.0% (95%CI = 96.8–99.9) and 98.3% (95%CI = 96.6–99.2) for urine samples and 99.4% (95%CI = 96.5–100.0) and 98.6% (95%CI 97.5–99.2) for cervical swabs, respectively. For NG detection, the sensitivity and specificity of the Xpert test were 99.2% (95%CI = 94.9–100.0) and 100.0% (95%CI = 99.0–100.0) for urine and 100% (95%CI = 92.8–100.0) and 99.7% (95%CI = 99.0–99.9) for cervical swabs, respectively. Conclusion The Xpert CT/NG test exhibited high sensitivity and specificity in the detection of CT and NG in both urine and cervical samples when compared to the reference results. The 90-min turnaround time for CT and NG detection at the point of care using Xpert may enable patients to receive treatment promptly.